Macroinvertebrados associados à macrófitas aquáticas em lagoas intermitentes no semi-árido - Souza, Bruno Barros de (2012)
This study proposed to assess how the structureis abiotic community in atemporary aquatic ecosystem of bioma Caatinga. Two species of aquatic macrophytes present in three temporary reservoirs Hydrocleys parviflora Seub. (Alismataceae) and Egeria densa (Hydrocharitaceae) from three lagoon are located in the zone of damping, outside of protected Unit Conservation Natural Monument Grota do Angico, Sergipe-Brazil. The macrophytes and associated macroinvertebrates were sampled in Surber 0.25 mm for a period of four months, from June to September 2011, during which the lakes were full. Samples of macrophytes were repeated at intervals of fifteen days, as well as variables measured were physical - chemical: pH, DO, water temperature, salinity, volume, transparency, concentration of phosphate and nitrate from water by the multiparameter instrument mod. Hanna HI. The macrophytes and macroinvertebrates were preserved in alcohol 70%. After analysis of macroinvertebrates and identified at taxonomic family. It was determined the weight per capita biomass of aquatic macrophytes. The abiotics variable had presented significant differences between the lagoons, how much to the space distribution of the macrophytes, it observed a relation of codominnace in a lagoon and dominance of H. parviflora in others two. The average biomass of dominant H. parviflora was estimated: 64,84±30,52 g.m-² and E. densa was 79,25±30,27 g.m-² (n = 36 and 18) respectively, however statistically had not significance variation between lagoons. The macroinvertebrates (4668 individuals) are distributed in 31 families belonging to four classes: Insecta> Hirundinidae> Gastropoda> Aracnidae. The class Insecta showed the highest abundance (45.40%) followed by the Hirundinidae (40.70%) of individuals sampled. The application of canonical correlation analysis found no significant relationships between the abiotic factors and the presence of most families of macroinvertebrates. The lagoons presented high levels of nutrients which indicate a process of eutrophication, but the presence of aquatic macrophytes, common in natural and artificial lakes in the semiarid, suggests that its functional role has attenuated this process. We did not find any relationship between macroinvertebrate diversity and different species of macrophytes present. The macrophytes, however, influenced the homogeneity of communities, softening the variations both in time scale as a function of more dramatic changes in the physical environment. The lakes with higher macroinvertebrates richness were more stable than the one that occurrence only one species. These ponds are the predominance of pollution tolerant species, and a large proportion of predators, especially the latter, a response to the large supply of prey.